The language of security in Philippine-US relations - Misalucha, Charmaine G. (Animo Repository, 2014)
There is a need to reformulate the way in which we view international relations. Rather than simply a play at an obscure theater with the same characters reprising their respective roles based on an old script, international relations need to be seen as a play at the world stage whose script is always being reviewed, revised, rewritten, and renegotiated by characters who are actively searching for ways to be accommodated. In this way, the characters and the roles they play are provisional: they become who or what they are because of actions they take, and not necessarily because they are fated to be revered or condemned. To achieve the fluid nature of this script, one must pay attention to language games. These games allow for the participation of both sides of the equation - the Philippines and the United States - in the creation of the structure and direction of their relationship. © 2014 Koninklijke Brill NV, Leiden, The Netherlands.